Determination of the positions of aluminum atoms introduced into SSZ-35 and the catalytic properties of the generated Brønsted acid sites. Issue 9 (15th February 2017) - Miyaji, Akimitsu; Kimura, Nobuhiro; Shiga, Akinobu; Hayashi, Yoshihiro; Nishitoba, Toshiki; Motokura, Ken; Baba, Toshihide
Abstract : Al atoms were introduced into three of the four possible sites with constant proportions in the zeolite SSZ-35 lattice. Abstract : The positions of aluminum (Al) atoms in SSZ-35 together with the characteristics of the generated protons were investigated by 27 Al multiple quantum magic-angle spinning (MQ-MAS), 29 Si MAS, and 1 H MAS NMR data analyses accompanied by a variable temperature 1 H MAS NMR analysis. The origin of the acidic –OH groups (Brønsted acid sites) generated by introducing Al atoms into the T sites was investigated and the T sites introduced into the Al atoms were revealed. To further determine the catalytic properties of the acidic protons generated in SSZ-35, the influence of the concentration of the Al atoms on the catalytic activity and selectivity during the transformation of toluene was examined.